Willingness of Residents to Participate in UAE Heritage and Culture Tourism Industry - Obaid Rashid Aldhanhani, Howaidah Mohamed; Zainudin, Mohamad Zahir (International Journal of Sustainable Construction Engineering and Technology, 2022)
Heritage and culture tourism is very cruicial to the economic development of a country. Thus, it is essential that native people should have knowledge about heritage and culture so that they able to spread the knowledge by taking advantage of the media channel. The current study assessed the willingness of the UAE residents on the heritage and culture tourism of UAE. hence, this paper presents a quantitative study to assess the willingness of UAE residents to involve in heritage and culture tourism of their country. A questionnaire survey was conducted to gauge 11 questions related to heritage and culture tourism from the participants in terms of their level of agreement using 5-points Likert scale.  A total of 558 questionnaire samples were distributed however 501 completed questionnaire forms were collected and analysed. The analysis found that majority of the respondents has basic information regarding heritrage and tourism of the UAE. They are interested and willing to know more about the heritage and culture of the UAE. A significant number of respondents mentioned that they wish to visit UAE heritage with their family. It was also pointed out by the respondents that they have not experience all types of tourism to heritage locations in UAE. The findings from this study emphasis the need of promoting more about the heritage eventhough the media has  playing very important role in distributing awareness and knowledge regarding heritage and tourism of the UAE.